Widespread pH abnormalities in patients with malformations of cortical development and epilepsy: a phosphorus-31 brain MR spectroscopy study - Andrade, Celi Santos; Garcia Otaduy, Maria Concepcion; Ramos Valente, Kette Dualibi; Park, Eun Joo; Kanas, Alexandre Fligelman; Moreira da Silva Filho, Mauricio Ricardo; Tsunemi, Miriam Harumi [UNESP]; Leite, Claudia Costa (Elsevier B.V., 2014)
Introduction: Neuroimaging studies demonstrate that not only the lesions of malformations of cortical development (MCD) but also the normal-appearing parenchyma (NAP) present metabolic impairments, as revealed with H-1-MRS. We have previously detected biochemical disturbances in MCD lesions with phosphorus-31 magnetic resonance spectroscopy (P-31-MRS). Our hypothesis is that pH abnormalities extend beyond the visible lesions. Methods: Three-dimensional P-31-MRS at 3.0 T was performed in 37 patients with epilepsy and MCD, and in 31 matched-control subjects. The patients were assigned into three main MCD subgroups: cortical dysplasia (n = 10); heterotopia (n = 14); schizencephaly/polymicrogyria (n = 13). Voxels (12.5 cm(3)) were selected in five homologous regions containing NAP: right putamen; left putamen; frontoparietal parasagittal cortex; right centrum semiovale; and left centrum semiovale. Robust methods of quantification were applied, and the intracellular pH was calculated with the chemical shifts of inorganic phosphate (Pi) relative to phosphocreatine (PCr). Results: In comparison to controls and considering a Bonferroni adjusted p-value <0.01, MCD patients presented significant reduction in intracellular pH in the frontoparietal parasagittal cortex (6.985 +/- 0.022), right centrum semiovale (7.004 +/- 0.029), and left centrum semiovale (6.995 +/- 0.030), compared to controls (mean values standard deviations of 7.087 +/- 0.048, 7.096 +/- 0.042, 7.088 +/- 0.045, respectively). Dunnet and Dunn tests demonstrated that the differences in pH values remained statistically significant in all MCD subgroups. No significant differences were found for the putamina. Conclusion: The present study demonstrates widespread acidosis in the NAP, and reinforces the idea that MCD visible lesions are only the tip of the iceberg. (C) 2014 The Japanese Society of Child Neurology. Published by Elsevier B.V. All rights reserved.
Keywords: Malformations of cortical development; Epilepsy; Neurometabolism; Phosphorus spectroscopy; Magnetic resonance imaging